The Epidemiology, Presentation, and Outcome of Acute Post-infectious Glomerulonephritis in North East India: A Single Centre Experience: Post-infectious Glomerulonephritis in North East India - Barman, Himesh; Sangla, Lima; Dey, Biswajit; Ksoo, Rosina; Valarie Lyngdoh, Wihiwot; De, Manisha (Journal of Pediatric Nephrology, 2022)
Background and Aim: Acute post-infectious glomerulonephritis (PIGN) can occur due to various etiologies. Among these, post-streptococcal glomerulonephritis is the common cause. Though the burden has drastically decreased over the years in developed nations, it remains a reason for concern in developing countries. This study aimed to document the burden, clinical presentation, etiology, and outcome of PIGN referred to a tertiary care center in a developing country. Methods: This retrospective study was conducted in a tertiary care teaching hospital in northeast India. All cases diagnosed with acute PIGN were included in the study. Cases with an alternate diagnosis and cases with incomplete records were excluded from the study. Data on relevant clinical, demographic, and laboratory variables were extracted from the case records and discharge summary. Simple descriptive statistics, such as frequency and proportion were used. Results: A total of 202 cases of PIGN were included in the study. The Mean±SD annual admission rate was 22.4±6.1 per year. The Mean±SD age at presentation was 10.0±3.9 years and the male to female ratio was 1.2 to 1. The most common clinical features at the time of presentation were hypertension in 183 patients (90.59%), edema in 168 (83.16%), history of oliguria in 146(72.27%), and hematuria in 168 patients (83.2%). Proteinuria was present in 95 cases (47.03%). Either clinical or serological evidence of preceding streptococcal infection was observed in 160 children (83.2 %). Two cases had scrub typhus and one case had hepatitis B seropositivity. Hypertensive encephalopathy and left ventricular failure were observed in 20(9.90%) and 44 children (21.78%), respectively. Admission to the pediatric intensive care unit was required in 28.21%. No mortality was observed. Conclusion: PIGN constitutes a significant burden in this part of India. The incidence of complications was high but the outcome was good with adequate acute care.